Improving purchasing process for small purchases at a manufacturing company in chemical industry - Lehtinen, Esko (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This thesis was conducted on assignment by a multinational chemical corporation as a case study. The purpose of this study is to find ways to improve the purchasing process for small purchases at the case company. The improvements looked after are mainly cost and time savings. Purchasing process is the process that starts from the requisition of goods or services and ends when the invoice is paid. In this thesis the purchases with value less than 1000€ are considered to be small. The theoretical framework of the thesis consists of general theoretical view of costs and performance of the purchasing process, different types of purchasing processes and a model for improving purchasing processes. The categorization to small and large purchases is the most important followed by the division between direct and indirect purchases. Also models that provide more strategic perspective for categorization were found to be useful. Auditing and managerial control are important parts of the purchasing process. When considering the transaction costs of purchasing from the costs–benefits perspective large and small purchases should not have the same processes. Purchasing cards, e-procurement and vendor managed inventory are seen as an alternative to the traditional purchasing process. The empirical data collection was done by interviewing the company employees that take part of the purchasing process in their daily work. The interviews had open-ended questions and the answers were coded and analyzed. The results consist of process description and assessment as well as suggestions for potential improvements. At the case company the basic purchasing process was similar to the traditional purchasing process that is entirely done with computers and online. For some categories there was already more sophisticated e-procurement solutions in use. To improve the current e-procurement based solutions elimination of authorization workflow and better information exchange can be seen as potential improvements for most of the case purchases. Purchasing cards and a lightweight form of vendor managed inventory can be seen as potential improvements for some categories. Implementing the changes incurs at least some cost and the benefits might be hard to measure. This thesis has revealed that the small purchases have potential for significant cost and time savings at the case company.